2018
DOI: 10.1186/s12864-018-4627-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and secretome analysis of Aspergillus fumigatus in the presence of sugarcane bagasse

Abstract: BackgroundSugarcane bagasse has been proposed as a lignocellulosic residue for second-generation ethanol (2G) produced by breaking down biomass into fermentable sugars. The enzymatic cocktails for biomass degradation are mostly produced by fungi, but low cost and high efficiency can consolidate 2G technologies. A. fumigatus plays an important role in plant biomass degradation capabilities and recycling. To gain more insight into the divergence in gene expression during steam-exploded bagasse (SEB) breakdown, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 95 publications
6
43
0
1
Order By: Relevance
“…Whilst the pectin content in SB and SH is considerably lower than for hollocellulose ( de Souza Moreira et al, 2013 ; Li et al, 2017 ), evidence was also observed for pectin degradation on both, with considerable exclusive up-regulation of genes on SH likely reflecting differences in pectin content between the different carbon sources. Up-regulation of genes related to pectinolytic activity have also been reported previously on SB for A. niger (PL4 family), A. fumigatus (PL4 family) and for A. tamarii (PL1, PL9, GH28 families) ( Borin et al, 2017 ; de Gouvêa et al, 2018 ; Midorikawa et al, 2018 ). Genome-predicted enzyme profiles in Aspergillus sections Aspergillus, Candidi and Flavi indicate the presence of pectin-degrading enzymes in the GH families 28, 43, 53, 78, and 142, in the CE family 8, and in the PL families 1, 3, 4, and 26, again with considerable conservation in up to 15 species ( Barrett et al, 2020 ).…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Whilst the pectin content in SB and SH is considerably lower than for hollocellulose ( de Souza Moreira et al, 2013 ; Li et al, 2017 ), evidence was also observed for pectin degradation on both, with considerable exclusive up-regulation of genes on SH likely reflecting differences in pectin content between the different carbon sources. Up-regulation of genes related to pectinolytic activity have also been reported previously on SB for A. niger (PL4 family), A. fumigatus (PL4 family) and for A. tamarii (PL1, PL9, GH28 families) ( Borin et al, 2017 ; de Gouvêa et al, 2018 ; Midorikawa et al, 2018 ). Genome-predicted enzyme profiles in Aspergillus sections Aspergillus, Candidi and Flavi indicate the presence of pectin-degrading enzymes in the GH families 28, 43, 53, 78, and 142, in the CE family 8, and in the PL families 1, 3, 4, and 26, again with considerable conservation in up to 15 species ( Barrett et al, 2020 ).…”
Section: Discussionsupporting
confidence: 75%
“…With AA9, AA11, AA13, AA14, and AA16 exclusive to fungal genomes, multiple genes encoding LPMOs appear to be common in fungal genomes, particularly in Ascomycetes and Basidiomycetes ( Kracher et al, 2016 ). With previous reports of LPMOs in transcriptome and/or secretomes of A. niger , A. fumigatus, and A. tamarii following growth on sugarcane bagasse ( Borin et al, 2015 , 2017 ; de Gouvêa et al, 2018 ; Midorikawa et al, 2018 ), and recent characterization of seven AA9s in the secretome of A. terreus on soybean spent flakes ( Pierce et al, 2017 ), investigation here also highlights their involvement in the degradation of the SB and SH, with one AA3 gene and five LPMO AA9 genes up-regulated on both SB and SH lignocellulosic carbon sources, as well as exclusive AA3, AA7 and AA9-encoding genes on SB. Such data highlights potential conserved functional roles in biomass degradation, as reported in other fungi ( Isaken et al, 2014 ), as well as evidence for substrate specific activity, as documented recently for AA9 LPMOs ( Jagadeeswaran et al, 2016 ; Hüttner et al, 2019 ).…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations